2009
DOI: 10.1186/gb-2009-10-11-r130
|View full text |Cite
|
Sign up to set email alerts
|

BioGPS: an extensible and customizable portal for querying and organizing gene annotation resources

Abstract: BioGPS is a community based customisable gene annotation portal bringing together gene annotation resources on to a single platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
1,239
1
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,256 publications
(1,305 citation statements)
references
References 25 publications
57
1,239
1
8
Order By: Relevance
“…6). Gpr111 was mainly expressed in skin and heart, and very weakly in lung and spleen, which is consistent with large-scale microarray datasets (Wu et al, 2009). To corroborate receptor expression within these tissues, Gpr111 LacZ/LacZ mice were stained with X-Gal.…”
Section: Gpr111 and Gpr115 Are Expressed In Squamous Epitheliasupporting
confidence: 86%
See 1 more Smart Citation
“…6). Gpr111 was mainly expressed in skin and heart, and very weakly in lung and spleen, which is consistent with large-scale microarray datasets (Wu et al, 2009). To corroborate receptor expression within these tissues, Gpr111 LacZ/LacZ mice were stained with X-Gal.…”
Section: Gpr111 and Gpr115 Are Expressed In Squamous Epitheliasupporting
confidence: 86%
“…Previous transcriptional profiling indicated that Gpr116 is expressed in lung, placenta, heart, and eyecup, whereas Gpr110 transcript was found in cornea, liver, and ciliary bodies (Wu et al, 2009).…”
Section: Gpr116 Is Ubiquitously Expressed and Gpr110 Is Expressed Inmentioning
confidence: 99%
“…Indeed, it is conceivable that cGASexpressing cells generate cGAMP and provide it in trans to STING-expressing, but cGAS-incompetent cells, further amplifying antiviral gene expression in the context of TREX1 deficiency. In line with this concept, it is interesting to note that human cGAS and STING do not follow a tight coexpression pattern across different cell types, with cGAS showing a far more restricted expression pattern than STING (19)(20)(21). On a similar note, it is also possible that differential expression of connexins contributes to the unique confinement of disease activity to distinct tissues in the context of TREX1 deficiency.…”
Section: Discussionmentioning
confidence: 85%
“…25 Four AAC isoforms have been identified in human with distinct expression patterns. 26,27 According to previous reports, [28][29][30] AAC2 and AAC3 are the dominant AACs in ECs. Co-IP confirmed that ISM interacts with AAC2/AAC3 (Figure 5a).…”
Section: Resultsmentioning
confidence: 93%